FAKTOR-FAKTOR YANG MEMPENGARUHI PERSALINAN DENGAN TINDAKAN EKSTRAKSI VAKUM DI RSIA KASIH IBU KABUPATEN PURWOREJO: FAKTOR-FAKTOR YANG MEMPENGARUHI PERSALINAN DENGAN TINDAKAN EKSTRAKSI VAKUM DI RSIA KASIH IBU KABUPATEN PURWOREJO - Sholichah, Nur; Aisyah, Nirmala Ayu (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2023)
ABSTRACT Vacum extraction in labor aims to help the labor process that is experiencing complications. In a preliminary study at RSIA Kasih Ibu of Purworejo Regency in September 2020-2021 there were 38 maternity mothers with vacuum extraction in labor. To know the factors that influence of vacuum extraction in labor at RSIA Kasih Ibu of Purworejo Regency. Research design with survey analysis with a study appoarch case control. Sampling retrieval total sampling. Total 76 samples. Statistic test with chi-square. There is no relationship between age of vacuum extraction in labor (p value 0,425). There is a relationship between parity of vacuum extraction in labor (p value 0,000). There is a relationship between education of vacuum extraction in labor (p value 0,025). There is a relationship between long stage II of vacuum extraction in labor (p value 0,000). There is no relationship between age of vacuum extraction in labor. There is a relationship between parity, education, and long stage II of vacuum extraction in labor. For health workers to always improve training on childbirth so that the risk of vacuum extraction can be resolved. Key words: Age, Parity, Education, Long Stage II, Vacuum Extraction